2020
DOI: 10.1182/blood.2019003105
|View full text |Cite
|
Sign up to set email alerts
|

Altered microRNA expression links IL6 and TNF-induced inflammaging with myeloid malignancy in humans and mice

Abstract: Aging is associated with significant changes in the hematopoietic system, including increased inflammation, impaired hematopoietic stem cell (HSC) function, and increased incidence of myeloid malignancy. Inflammation of aging (“inflammaging”) has been proposed as a driver of age-related changes in HSC function and myeloid malignancy, but mechanisms linking these phenomena remain poorly defined. We identified loss of miR-146a as driving aging-associated inflammation in AML patients. miR-146a expression declined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 69 publications
2
44
0
Order By: Relevance
“…Notably, circulating miR-146a levels significantly decline with age and chronic age-related diseases and conditions, such as type 2 diabetes and frailty (Mensà et al, 2019; Ong et al, 2019). Current literature agrees about its pivotal role in inflammaging and age-related diseases (Grants et al, 2020). We recently suggested that the features of the current pandemic strongly suggest a role of inflammaging in worse COVID-19 outcomes, which mainly affect old people affected by age-related diseases (Bonafè et al, 2020; Storci et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Notably, circulating miR-146a levels significantly decline with age and chronic age-related diseases and conditions, such as type 2 diabetes and frailty (Mensà et al, 2019; Ong et al, 2019). Current literature agrees about its pivotal role in inflammaging and age-related diseases (Grants et al, 2020). We recently suggested that the features of the current pandemic strongly suggest a role of inflammaging in worse COVID-19 outcomes, which mainly affect old people affected by age-related diseases (Bonafè et al, 2020; Storci et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…The pivotal role of miR-146a-5p has been reported in a number of cell types that orchestrate the inflammatory response, including endothelial cells (Mensà et al, 2019; Olivieri et al, 2013a), microglial cells (Liu et al, 2020b), monocytes and macrophages, (Li et al, 2015; Zhou et al, 2019), and adipocytes (Roos et al, 2016). Recently, a reduced expression of miR-146a-5p was observed in a subgroup of patients affected by acute myeloid leukemia with inflammaging and poor outcome (Grants et al, 2020). Therefore, on the basis of the current literature, a decline in miR-146a-5p levels would be expected to unleash the release of inflammatory cytokines, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These features are also observed in aged wild-type mice and are associated with a skewing towards the myeloid lineage and a reduced proliferative capacity of HSCs 50 , 51 . Loss of microRNA-146a (miR-146a) in HSCs with ageing also promotes a myeloid bias 52 . Furthermore, myeloid cells derived from miR-146a-deficient HSCs have elevated levels of both IL-6 and tumour necrosis factor (TNF) 52 , which connects altered regulation of transcription in HSCs to inflammation.…”
Section: Vascular Extrinsic Mechanismsmentioning
confidence: 99%
“…Loss of microRNA-146a (miR-146a) in HSCs with ageing also promotes a myeloid bias 52 . Furthermore, myeloid cells derived from miR-146a-deficient HSCs have elevated levels of both IL-6 and tumour necrosis factor (TNF) 52 , which connects altered regulation of transcription in HSCs to inflammation. Overall, these studies indicate that ageing has effects on HSCs via several complex pathways that lead to reduced HSC function.…”
Section: Vascular Extrinsic Mechanismsmentioning
confidence: 99%
“…Inflammation is an increasingly accepted feature of MDS [ 102 , 103 , 104 ]. Different aspects of inflammation and associated dysregulated chronic immune responses have been found to play a role (age-related inflammation, disease-associated intrinsic and extrinsic inflammation).…”
Section: Aspects On Iron Hepcidin Inflammation and Mdsmentioning
confidence: 99%